Art School Building: the Old/New Chelsea. (June 2014) - Howarth, Lucy
Abstract In the wake of the recent demolition of the 1965 Chelsea School of Art building on Manresa Road in London, this article seeks to explore the relationship between art school architecture and art school pedagogy. Research on art school buildings, both national and international, and British art school education of the 1960s, is brought to bear, on the former 'New School of Art in Chelsea' building. In addition to an account of how this building came about, drawn from archival records and interviews with architects and former Chelsea students and staff, the correlation of utopianist values in post‐war British society, modernist architecture and higher education in art is examined. The reports of the National Advisory Council on Art Education (NACAE), which, in the 1960s, ushered in fundamental changes to British art education, are touched upon, and an account of the building design developed between art educationalists (including Chelsea Principal Lawrence Gowing and Chairman of the NACAE William Coldstream) and architects of the London County Council, is given. Photographs of the building, in the 1960s and during its demolition in 2010, are included. In addition to a historical account and case‐study, and despite the difficulties inherent, art school building is approached as an imaginative and socio‐political gesture, as a utopian act; 'art school building' in both senses ('building' as a verb and as a noun).